Testamenty urozených žen doby baroka. Několik poznámek k tématu - Kristina Swiderová (Theatrum Historiae)
The article is based on set of accounts left by noblewomen of the Bohemian Kingdom in the period of 1650–1753. Using a combination of quantitative and qualitative analysis confronted with prescriptive document ́s point of view, it tries to find out the meaning of testament in noblewomen’s lives. It deals with the formal structure and terms of last wills, such as property settlement, which was usually the main reason for testaments being composed. Particular attention is paid to the matter of servants, for the testament could have meant a complete change of their existence. In the early modern period, however, last will was the document standing on the very edge of one’s life, dealing with both the past and the future – the afterlife. The main emphasis is therefore laid on the testamentary piety, which is perceived among others as a means of the legitimization of the nobility itself, for which the process of the adjustments before death was well suited.